Children’s Self-Reports of Pain Intensity: Scale Selection, Limitations and Interpretation - Carl L von Baeyer (Pain Research and Management)
Most children aged five years and older can provide meaningful self-reports of pain intensity if they are provided with age-appropriate tools and training. Self-reports of pain intensity are an oversimplification of the complexity of the experience of pain, but one that is necessary to evaluate and titrate pain-relieving treatments. There are many sources of bias and error in self-reports of pain, so ratings need to be interpreted in light of information from other sources such as direct observation of behaviour, knowledge of the circumstances of the pain and parents’ reports. The pain intensity scales most commonly used with children – faces scales, numerical rating scales, visual analogue scales and others – are briefly introduced. The selection, limitations and interpretation of self-report scales are discussed.